THE STRATEGY OF NETFLIX TO DOMINATE THE ENTERTAINMENT MEDIA MARKET IN INDONESIA 2016-2021 - Atiqa Rana Fergus Putri; Arie Kusuma Paksi (Jurnal Ilmiah Dinamika Sosial, 2021)
Multinational corporations (MNCs) are non-state actors who have a significant role in international relations. Globalization has facilitated the development of MNCs as well as the transformation of media. It impacts the presence of multinational entertainment media companies operating with the SVOD (Subscription video-on-demand) system like Netflix. Netflix chooses Indonesia as one of its potential markets. However, Netflix has to face new competitors and resolve several obstacles and regulations from other companies and governments in Indonesia. This research aims to find out and analyze the strategy of Netflix is dominating the Entertainment Media market in Indonesia with the concept of MNC, international strategy, and competitive advantages. This research used a qualitative approach with descriptive methods where the data collection came from secondary data such as books, academic literature, and news portals. In data analysis, the researcher reviewing and draw an explanation regarding the phenomenon. The strategies and efforts made by Netflix can make Netflix become the number one choice for the SVOD platform in the Indonesian market based on the supremacy that Netflix has, especially in providing original content. By developing its strategy, Netflix can continue to internationalize its product services in the Indonesian market. Keywords: Netflix, Strategy, Subscription Video on Demand (SVOD), Indonesia, Multinational Corporations (MNC)